UJI AKTIVITAS ANTIBAKTERI SARI BUAH SAWO MANILA (Manilkara zapota (L.) van Royen) MUDA DAN MASAK TERHADAP BAKTERI Escherichia coli - MELZI OCTAVIANI (Jurnal Penelitian Farmasi Indonesia, 2017)
The antibacterial activity of the Manila Fruit Juice (Manilkara zapota (L.) van Royen) Raw and Ripe againt Escherichia coli bacteria has been done with a solid dilution method. The purpose of this research is to know and compare the antibacterial activity of fruit juice sawo manila raw and ripe to inhibit the growth of Escherichia coli bacteria. The results of the Antibacterial Activity of Manila (Manilkara Zapota (L.) van Royen) Raw with a concentration of 100%, 80%, 60%, 40% and 20%, respectively, of 120 colonies/ml colonies, 154 colonies/ml, 179.33 colonies/ml, 195.33 colonies/ml and 196.67 colonies/ml with an average number of early colonies of bacteria 197.67 colonies/ml. The results shown that the concentration of 100% will be decreasing of 39% the colony. While, the antibacterial activity test’s results of manila fruit juice (Manilkara zapota (L.) van Royen) ripe with 100%, 80%, 60%, 40% and 20%, respectively, with the average number of colony 221.00 colonies/ml, 221.67 colonies/ml, 221.67 colonies/ml, 221.67 colonies/ml and 221.67 colonies/ml with an average number of early colonies of bacterial 222.00 colonies/ml. This indicated that the raw manila has antibacterial activity, while the manila ripe fruit juice shown no antibacterial activity against bacteria of Escherichia coli.